Factors Associated with Caregiving Behavior of Family Caregivers of Children with Cerebral Palsy in Bangkok - ปัญญาธนคุณ ณัฐธิดา; ธีระทองคำ แสงทอง; สกุลหงส์โสภณ สมนึก (Thai Journal of Nursing and Midwifery Practice, 2019)
Abstract: This correlational research study aimed at examining the factors related to caregiving behavior of family caregivers of children with cerebral palsy. Seventy five participants were family caregivers of children with cerebral palsy in Bangkok. Data were collected by seven structured interview questionnaires based on Bandura’s conceptual framework, including personal factors of children with cerebral palsy and their family caregivers, knowledge of cerebral palsy and care, beliefs of rehabilitation, perceived self-efficacy in care, social support, and caregiving behavior for children with cerebral palsy. Data were analyzed using descriptive statistics, Pearson Product Moment Correlation, Spearman’s Rank-Order Correlation, and Chi-square test. Results revealed that mean score of caregiving behaviors of family caregivers of children with cerebral palsy were at a high level (X= 124.12, SD = 10.55). Only perceived self-efficacy was positively significant correlated with caregiving behaviors of family caregivers of children with cerebral palsy (r = .371, p<.05). The results suggest that registered nurses should promote perceived self-efficacy for family caregivers of children with cerebral palsy in order to enhance their confidence to confront and to solve problems resulting in better care and well-being of children with cerebral palsy and their families.